2019
DOI: 10.2984/73.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Impacts of Pacific Island Invasive Species. 15. Psittacula krameri, the Rose-Ringed Parakeet (Psittaciformes: Psittacidae)

Abstract: The rose-ringed parakeet (RRP), Psittacula krameri, has become established in at least four Pacific Island countries (Hong Kong China, Japan, New Zealand, U.S.A.), including the Hawaiian islands of Kaua'i, O'ahu, and Hawai'i. Most Pacific islands are at risk of RRP colonization. This species was first introduced to Hong Kong in 1903 and Hawai'i in the 1930s-1960s, established since 1969 in Japan, and in New Zealand since 2005 where it has repeatedly established after organized removals. The founding birds were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…syringa Melia azedarach, Natal fig Ficus natalensis, and pawpaw Carica papaya fruit/ flower throughout the year. Similar studies also found that parakeets are mainly frugivores and granivores (Clergeau and Vergnes 2011;Klug et al 2019;Shiels and Kalodimos 2019;Borray-Escalante et al 2020). We also observed the parakeets feeding on insects such as carpenter ants throughout the year as a supplementary dietary item.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…syringa Melia azedarach, Natal fig Ficus natalensis, and pawpaw Carica papaya fruit/ flower throughout the year. Similar studies also found that parakeets are mainly frugivores and granivores (Clergeau and Vergnes 2011;Klug et al 2019;Shiels and Kalodimos 2019;Borray-Escalante et al 2020). We also observed the parakeets feeding on insects such as carpenter ants throughout the year as a supplementary dietary item.…”
Section: Discussionsupporting
confidence: 88%
“…This may potentially limit the spread of these alien species in South Africa. However, Shiels and Kalodimos (2019) reported that parakeets could reduce the tree's ability to reproduce when they forage in large flocks. Little has been reported on the parakeets spreading alien invasive species as they typically predate on seeds with diameter ≥ 2.5 cm (Dhindsa et al 1992;Ahmad et al 2011;Shiels et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Self-sustaining populations of Rose-ringed Parakeets, for instance, have to date been recorded in over 35 countries across Europe, North America, the Middle East and Southern Africa (GISD 2020b). Concerns over the negative impacts of these populations have prompted eradication efforts but these have often proved challenging and there have been calls for greater regulation of international trade to prevent further spread (Shiels and Kalodimos 2019). Rose-ringed Parakeets were the species most commonly observed in our study and were often featured in large numbers.…”
Section: Resultsmentioning
confidence: 99%
“…Introduced populations of rose-ringed parakeets have led to negative impacts on native natural resources, economies, and human health and safety. Ecological impacts of invasive rose-ringed parakeets include potential habitat alteration, invasive seed spread, resource competition, and injury and death of native wildlife from the parakeet's highly antagonistic behavior (Shiels and Kalodimos 2019). In Australia, invasive rose-ringed parakeets strip tree bark which has led to tree death (Fletcher and Askew 2007).…”
Section: Introductionmentioning
confidence: 99%